The Role of Information Technology on job Performance analytical study to sample of private Iraqi banking managers answers and relationships with their personal characters The Role of information technology on job performance - شريف, اثير انور; عودة, بلال كامل (Journal of Economics and Administrative Sciences, 2016)
Abstract:Purpose\The researcher paper aims to determine the impact of information technology on the job performance, for Iraq private ban as through the use of technology dimensions of job performance.The aim of this research: this study aims to discuss the importance of information technology and its role in achieving job performance and its impact on the Iraq banking sector design/ methodology/ approach used entrance design/methodology/approach- pilot, the questionnaire was used to collect data in order to develop a model to measure reliably and correctly to the variables of information technology and job performance, and hypotheses were tested through the use of some statistical treatments.Results findings\ the study found a relationship with semantic differences between the use of information technology and functionality for employees, and the study pointed to Zerorh work on the modernization and development of the IT infrastructure information permanently and continuously and P is proportional nature of the work and also computer connectivity AldakhThe practical implications: this research provides a useful measure of the development of the relationship between information technology, it helps managers to use to assess the current situation in the capabilities of the performance of banks. Managers may improve their performance regulatory programs more effectively and efficiently through strategic orientation towards competition.Originally /value originally / value- undertake this research assisted service providers in the banking sector to address the challenge of the basic practices of information technology order to achieve.